RETRACTED: Icariin Reduces Dopaminergic Neuronal Loss and Microglia-Mediated Inflammation in Vivo and in Vitro - Wang, Guo-Qing; Li, Dai-Di; Huang, Chun; Lu, Di-Sheng; Zhang, Chao; Zhou, Shao-Yu; Liu, Jie; Zhang, Feng (Frontiers in Molecular Neuroscience, 2018)
Parkinson’s disease (PD) is one of most common neurodegenerative diseases and characterized by a gradual loss of dopamine (DA) neurons in the substantia nigra (SN). An excessive inflammatory response in the central nervous system is essential for the pathogenesis of PD with the principal component of glial activation, especially microglia activation. Icariin (ICA), a single active component extracted from the Herba Epimedii, presents amounts of pharmacological activities such as anti-inflammation, anti-oxidant and anti-aging. In the present study, two different neurotoxins of 6-hydroxydopamine (6-OHDA) and lipopolysaccharide (LPS)-induced rat midbrain DA neuronal damage were performed to investigate the neuroprotective effects of ICA. In addition, primary rat midbrain neuron-glia co-cultures were applied to explore the mechanisms underlying ICA-exerted DA neuroprotection. Results indicated that ICA attenuated 6-OHDA and LPS-induced behavior changes, DA neuronal damage and microglia activation. Consistent neuroprotection were shown in midbrain neuron-glia co-cultures. Furtherly, in vitro studies demonstrated that ICA reduced LPS- and 6-OHDA-induced microglia activation and the subsequent production of pro-inflammatory factors through the inhibition of nuclear factor-κB (NF-κB) signaling pathway activation. Together, ICA could produce neuroprotection against LPS- and 6-OHDA-induced DA neurotoxicity both in vivo and in vitro through the inhibition of microglia-mediated neuroinflammation.